(untitled) (Comunicação & Inovação, 2017)
This article uses the big data concept to investigate which search terms typed on Google can indicate how internet users signify creativity. For this, a bibliographical survey of the communication works that use Google Trends was carried out, along with a content analysis of 50 search terms that included the term "creativity" in searches conducted in Brazil, by the main page of Google, between 2004 and 2014. The results show possible correspondences between the image of creativity and academic definitions.